The Influence of Experiential Learning Model on Primary School Student’s Creative Thinking Skills - Lutfi Asyari; Risma Nuriyanti; Dani Gunawan; Rajji K. Adiredja (Universitas Sebelas Maret, 2021)
The students’ skill in exploring creative ideas in writing is a problem that needs to be taken seriously. This happens because of the students’ lack of creative thinking in exploring some ideas in words. The purpose of this research was to examine the effects of experiential learning model on primary school students’ creative thinking skill. The method used quasi-experimental of non-equivalent control group design. The population of this research was a group of fourth grader students of Sekolah Dasar Labschool UPI (Labschool UPI Primary School) in total of 47 students and divided in to two separate classes, which were an experimental class and a control class. The results of this research revealed significant contrasts in post-test between an experimental class and a control class. The results concluded that the experiential learning model has significant effects on primary school students’ creative thinking skill. Therefore, the experiential learning model is one of the solutions for teacher to develop students’ creative thinking skill, especially in writing from the aspects of flexibility, fluency, originality and elaboration. Moreover, the outcome ideas were diverse, expressive and comprehensible.